"Attenuating Anxieties": A grounded theory study of mental health nurses' responses to clients with suicidal behaviour. Issue 5 (5th December 2018) - Morrissey, Jean; Higgins, Agnes
Abstract: Aims and objectives: To develop a grounded theory to explain mental health nurses' responses to clients with suicidal behaviour. Background: Mental health nurses are an integral part of the multi‐disciplinary teams supporting people who experience suicidal behaviour, yet limited research is available that explores how nurses respond to the needs of people at risk of suicide and what factors influence their responses and actions. Methods: Grounded theory was the methodology for this study. Interviews were conducted with 33 mental health nurses working in an urban area in the Republic of Ireland. Data were analysed using the concurrent processes of comparative analysis, theoretical sampling, theoretical sensitivity and memo writing. COREQ 32‐item checklist was used. Results: The core category from the data was "Attenuating Anxieties." Participants' main concerns about caring for suicidal clients were related to their feelings of professional and personal vulnerability and the need to protect clients and themselves. This theory "Attenuating Anxieties" highlights the way in which nurses allay their anxieties by utilising historically known risk adverse strategies to care for the suicidal person. Acquisition of further psychotherapeutic training, clinical supervision as well as increased reflexivity protected some participants and enabled them to work creatively and collaboratively while supporting and facilitating therapeutic risk‐taking. Conclusions: The theory of "Attenuating Anxieties" identifies how participants worked within the context of mental health as members of the "risk society, " wherein they worried about the possibility and probability of a negative or adverse effect for both the client and self, leaving them to feel constantly vulnerable and unsafe. Relevance to clinical practice: This theory highlights the need for a culture of openness that acknowledges nurses' and organisations' anxieties surrounding suicide and promotes a discourse among nurses that moves from a position of risk aversion to a relational and recovery‐orientated approach.